The Symbolic Power of Sleeping without Mattress Practice in Kasuran Village of Yogyakarta - Qudsy, Saifuddin Zuhri; Abdullah, Irwan; Qodir, Zuly (Al-Albab, 2017)
The work aims at exploring the practice of symbolic power of sleeping without kapok (matress) in a hamlet of Kasuran. It explores the process of reproduction of symbolic power and how it becomes a ritual practice preserved by the people of Kasuran. For many Kasuran people, Sunan Kalijaga saying is final. They understand and believe in his textual meaning by practising sleeping without matress ritual. The study finds that the reproduction of meaning of sleeping without mattress happens in the hands of agents that actively promote the myth about the saying of Sunan Kalijogo. They include Wartilah as the head of the hamlet (believing and promoting Sunan Kalijaga statement), Suharso as a pious man from Hindu tradition, secretary of the forum of harmony among religious blievers (believing that this myth is supposed to happen far before Sunan Kalijaga Era),  Juremi and Suwardi, the takmir (board management of mosque) that represent religious mass organization of Muhammadiyah and Nahdlatul Ulama (NU). Although the agents have different points of view in understanding the phenomenon, they actually maintain and preserve this kind of symbolic power to gain symbolic capital. This work also finds that the dynamic process of engineering and modification of living without mattress becoming living with spon mattress/springbed has been the results of the new interpretation by the people in the village. The latest is associated with spiritual, social and political engineering aspects of the practice.